2007
DOI: 10.1080/03056240701672619
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, Petroleum & Policy Intervention: Lessons from the Chad-Cameroon Pipeline

Abstract: The ‘resource curse’ – the tendency of resource wealth to impair natural resource exporting countries on various economic and political dimensions – has shown some of its strongest manifestations in Africa's petro-states. For this reason, the World Bank's recent attempt to engineer an accountable and transparent oil economy in one of Africa's poorest and most corrupt countries – Chad – deserves close scrutiny and critical analysis. Although the World Bank has conducted the Chad-Cameroon Pipeline Project with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Oil companies were not directly involved. The Chadian experiment yielded some positive societal benefits and it helped to insulate the country from the "resource curse" for several years (Gould and Winters 2007;Kojucharov 2007). …”
Section: Table 3 About Herementioning
confidence: 99%
See 2 more Smart Citations
“…Oil companies were not directly involved. The Chadian experiment yielded some positive societal benefits and it helped to insulate the country from the "resource curse" for several years (Gould and Winters 2007;Kojucharov 2007). …”
Section: Table 3 About Herementioning
confidence: 99%
“…While the programme yielded some economic and social benefits, academic research has demonstrated that it fell far short of the expected outcomes (Gould and Winters 2007;Kojucharov 2007;Pegg 2006 On the other hand, the World Bank failed to effectively create the mechanisms for overseeing the use of oil revenues (including a strong and well-resourced oversight committee) before the start of oil production in 2003. While World Bank officials emphasized the importance of "sequencing" (that means, encouraging capacity building before allowing oil infrastructure construction), pipeline construction already started four months after project approval and oil production started one year ahead of schedule.…”
Section: Table 4 About Herementioning
confidence: 99%
See 1 more Smart Citation
“…This body's purpose was the management of the revenues allocated to the priority sectors. Members of the Collège were appointed by the government, as well as by civil society through previously designed NGOs (Gould and Winters, 2007;Kojucharov, 2007). To complete the institutional setting, the first PRSP was finally approved in 2004 within the framework of the Heavily Indebted Poor Countries Initiative promoted by the WB and IMF.…”
Section: Discussionmentioning
confidence: 99%
“…According to Watts (2005, p. 5089), in Nigeria, ‘oil capitalism produces particular sorts of enclave economies and governable spaces characterised by violence and instability’. Even the highly touted US$4.2 billion World Bank funded Chad‐Cameroon ‘Petroleum Development and Pipeline Project’ that started in 2000 did not manage to reverse the so‐called ‘resource curse’ (Kojucharov 2007). The main problem was not the many violent disputes that characterise the Nigerian situation, but rather that ‘the tensions created by the World Bank's control of Chad's economic policies have transformed the CCPP [Chad/Cameroon Pipeline Project] from a joint development initiative into a fundamentally counterproductive struggle for authority’ (Kojucharov 2007, p. 489).…”
Section: The Political Economy Of Africa's Natural Resourcesmentioning
confidence: 99%